Karakteristik Suara Rhacophorus edentulus Mueller, 1894 Asal Pegunungan Mekongga, Sulawesi Tenggara (Anura: Rhacophoridae) - Kurniati, Hellen (Perhimpunan Biologi Indonesia, 2015)
Vocalizations Rhacophorus edentulus Mueller, 1894 have never been described before. The advertisement calls of four individual males of R. edentulus which originated from Mekongga Mountains, Southeast Sulawesi were recorded in December 7-8, 2010 at air temperatures of 20.5ÃÂ°C.ÃÂ Location of sound recording for the four individual males were performed at two different places, call of one individual was recorded when it was calling in a plastic bag in the base camp, while calls of the other three individuals were recorded in their habitat in the forest. Adobe Audition 3.0 software was used to visualize sound waves.ÃÂ Calls of R. edentulus have two types, i.e. pulses and pure tone.ÃÂ Sound wave of pulses has two types, namely pulse type 1 and pulse type 2; whereas sound wave of pure tone also has two types, namely pure tone type 1 and pure tone type 2.ÃÂ Based on the dominant frequency and the fundamental frequency of pure tones waves and pulse waves, the natural noise in the forest habitats affects the dynamics of the frequency of calls that were released by males R. edentulus; frequency sound with low noise is more dynamic than the frequency of the sound with high noise level.ÃÂ Key words: vocalization, Rhacophorus edentulus, Mekongga Mountains, Southeast Sulawesi.ÃÂ